VO2 attained during treadmill running: The influence of a specialist (400-m or 800-m) event - James, D. V. B.; Sandals, L. E.; Draper, S. B.; Maldonado-Martin, S.; Wood, D. M. (International Journal of Sports Physiology and Performance, 2007)
Previously it has been observed that, in well-trained 800-m athletes, VO2max is not attained during middle-distance running events on a treadmill, even when a race-type pacing strategy is adopted. Therefore, the authors investigated whether specialization in a particular running distance (400-m or 800-m) influences the VO2 attained during running on a treadmill. Methods: Six 400-m and six 800-m running specialists participated in the study.A 400-m trial and a progressive test to determine VO2max were completed in a counterbalanced order. Oxygen uptakes attained during the 400-m trial were compared to examine the influence of specialist event. Results: A VO2 plateau was observed in all participants for the progressive test, demonstrating the attainment of VO2max. The VO2max values were 56.2 ± 4.7 and 69.3 ± 4.5 mL · kg-1 · min-1 for the 400-m- and 800-m-event specialists, respectively (P = .0003). Durations for the 400-m trial were 55.1 ± 4.2 s and 55.8 ± 2.3 s for the 400-m- and 800-m-event specialists, respectively. The VO2 responses achieved were 93.1% ± 2.0% and 85.7% ± 3.0% VO2max for the 400-m- and 800-m-event specialists, respectively (P = .001). Conclusions: These results demonstrate that specialist running events do appear to influence the percentage of VO2max achieved in the 400-m trial, with the 800-m specialists attaining a lower percentage of VO2max than the 400-m specialists. The 400-m specialists appear to compensate for a lower VO2max by attaining a higher percentage VO2max during a 400-m trial.